Venous thromboembolism incidence and association with overall survival in pancreatic cancer: A Finnish nationwide cohort study - Panu Aaltonen; Harri Mustonen; Pauli Puolakkainen; Caj Haglund; Katriina Peltola; Olli Carpén; Riitta Lassila; Hanna Seppänen (Cancer Medicine)
Abstract Introduction Pancreatic cancer (PC) is associated with a high risk of venous thromboembolic events (VTEs). We investigated the incidence of VTE before and after the diagnosis of PC and its association with overall survival. Methods We identified PC patients diagnosed in 2013–2016 from the Finnish Cancer Registry. Data on healthcare visits and death were collected, along with follow‐up data through the end of 2020. We compared patients who underwent radical‐intent surgery (RIS) to those who underwent palliative treatment (PT) alone. Results We identified 4086 PC patients, of whom 343 (8.4%) underwent RIS and 3743 (91.6%) received PT. VTE incidence within 1 year before a PC diagnosis was higher in the PT (4.2%, n = 156) than in the RIS group (0.6%, n = 2; p < 0.001). The cumulative incidence of VTE at 12 and 24 months after a PC diagnosis was 6% (n = 21) and 9% (n = 31), respectively, within the RIS group, and 8% (n = 286) and 8% (n = 304) within the PT group. In the PT group, a VTE within 1 year before a PC diagnosis was independently associated with a worse survival {hazard ratio, HR 1.9 [95% confidence interval (CI) 1.6–2.2]}. In both groups, VTE after a PC diagnosis was associated with a worse survival [RIS group: HR 2.6 (95%CI 1.8–3.7) vs. PT group: HR 2.2 (95%CI 1.9–2.4)]. Conclusions A VTE within 1 year before a PC diagnosis more often occurred among PT PC patients than among patients who underwent RIS. VTE might serve as a diagnostic clue to detect PC at an earlier stage.